The Impact of Working Memory Training on Grammatical Development of Complex Sentences among Iranian EFL Intermediate Teacher Trainees - Molaei, Akbar (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the impact of working memory training on the grammatical development of complex sentence structures among Iranian EFL intermediate teacher trainees.Methods and Materials: A quasi-experimental design was employed involving 49 female freshman EFL teacher trainees from Bentol-hoda Teacher Education University in Bushehr, Iran. Participants were assigned to either an experimental group, which received structured working memory training over four weeks, or a control group, which received traditional grammar instruction. Both groups completed a grammar pre-test and post-test focused on complex sentence structures, including noun, adjective, and adverbial clauses. The same grammar test was used at both time points to assess changes in grammatical proficiency. Data were analyzed using Analysis of Covariance (ANCOVA), with the pre-test scores treated as covariates to determine the effect of the intervention.Findings: Descriptive statistics showed that while both groups had similar grammar scores at pre-test (M = 22.67, SD = 3.21 for experimental; M = 23.02, SD = 3.09 for control), the experimental group showed significantly higher gains in the post-test (M = 31.45, SD = 2.88) compared to the control group (M = 25.11, SD = 3.34). ANCOVA results confirmed a statistically significant effect of the working memory training on grammar achievement, F(1, 46) = 36.84, p = .000, η² = .45, indicating a large effect size. The covariate (pre-test score) was also significant, F(1, 46) = 21.56, p = .000, η² = .32.Conclusion: The findings demonstrate that structured working memory training can significantly enhance EFL learners’ grammatical development of complex sentence structures. This supports the integration of cognitive training components into grammar instruction in EFL teacher education programs, particularly in formal classroom settings with limited natural input.